Interview with Umm Zakiyyah - Quayum, Mohammad Abdul (Flinders University, Australia, 2018)
Umm Zakiyyah is one of the most prominent African-American Muslim writers writing about Muslims and Islam in the post-9/11 period. Her novels touch on the interfaith struggles of Muslims and Christians in a post-modern world and on the moral, spiritual and intercultural struggles of Muslims as minorities in a country where Muslims have been systematically marginalised after twin-tower attacks in 2001 and the subsequent American invasions of Afghanistan (2001) and Iraq (2003). She also writes about racism, women’s issues, the practice of Muslim women wearing headscarfs, and polygamy. In this interview, Umm Zakiyyah talks about her favourite writers, about the function of the writer in general, about the critical reception of her novels and about the influence of Islam on her imagination. She also addresses the issues of Islamophobia in the West, the future of Islamic fiction and questions pertaining to If I Should Speak and other novels.